Determination of Densities of Amino Compounds for Molar Volumes in Aqueous Solutions with Magnetic Float Densimeter at Various Temperatures (Biological Sciences - PJSIR, 2006)
Densities (r) of urea (H NCONH ), methylurea (H C-HNCONH ), melamine (C N H ) in aqueous, alongwith2                     2                                        3                                2                                    3     6    6mehtylurea in 0.05 mol kg-1  aqueous urea solutions have been measured with magnetic float densimeter (MFD) withf f                                                                                                   2 the accuracy value of 1x10-3 kg m-3. The data were used to calculate apparent molar volumes (Vf ) that are compared with the values obtained with Anton Paar densimeter DMA 60/601 model. The values of the r and Vf parameters were regressed and extrapolated to zero concentration (m = 0), for their limiting densities (ro) and limiting molar volumes (V o) alongwith their respective slope values. The values of the ro and V  oconstants elucidated the heteromolecular interactions of  -NH2 group, and it was noted that -NH     in different chemical compounds influenced interactions with water, especially with3 electron donating -CH  group of methylurea.